PRINSIP PERSOONLIJKE VERGUNNING PADA PELAKSANAAN PERATURAN KEPALA KEPOLISIAN RI NOMOR 9 TAHUN 2012 TENTANG PENERBITAN SURAT IZIN MENGEMUDI - Ni Made Liana Dewi; I Made Wahyu Chandra Satriana; Kadek Ery Kusumayanthi (Kerta Dyatmika, 2019)
A Driving Permit is a type of an individual license (Persoonlijke Vergunning), therefore a Driver's License for issuance requires certain conditions that are related to the conditions of a Driving License. In the Regulation of the Head of the Indonesian National Police No. 9 of 2012 Article 52 Paragraph 2 Regarding Driving License. Mention that the person authorized to issue a SIM (Driving License) to the public is the Chief of Police in each area and delegated to the Head of the Traffic Unit. The existence of the Klungkung Regional Police Headquarters is very much needed to provide legal awareness to the public on the importance of a SIM which is Persoonlij Vergunning based on the provisions of the Republic of Indonesia National Police Chief Regulation No. 9 of 2012 concerning Driving License. The first problem formulation is how is the principle of Persoonlijke Vergunning in the implementation of Perkap Polri No. 9 of 2012 concerning Driving License and the second Is the factor inhibiting the implementation of the Police Headquarters No. 9 of 2012 concerning Driving License.This research includes empirical legal research. Data Sources consist of Primary Data Sources, Secondary Data, Data collection techniques used in this study are interviews, data analysis used in this study is qualitative analysis. As for the discussion discussed namely the understanding of a driving license, the definition of service, the term police / police, the Persoonlijke Vergunning Principle from the perspective of a driving permit, the Relationship of a Driving License with the Authorized Authority to Manage Highway Traffic, Implementation of the Police Headquarters No. 9 of 2012 concerning Driving Permits at the Klungkung Police Station Traffic Sat, the effectiveness of the driving permit service (SIM) at the Klungkung Police Traffic Management Unit based on the Police Headquarters No. 9 of 2012 concerning Driving License, Factors inhibiting the implementation of the Police Headquarters No. 9 of 2012 concerning Driving License.Based on the results of research that have been reviewed and described, the conclusions that can be conveyed are as follows: The effectiveness of the driver's license service (SIM) at the Klungkung Regional Police Station is related to the Effectiveness of the Republic of Indonesia's National Police Chief Regulation Number 9 of 2012 Regarding Driving License, can run effectively in the service of a driver's license (SIM), if it can fulfill the effective element of the legal method of the Regulation of the Head of the Indonesian National Police Number 9 of 2012 concerning Driving License. Inhibiting factors in the implementation of Police Headquarters No. 9 of 2012 concerning Driving Licenses on the Klungkung Regional Police Station, namely legal cultural factors, and other inhibiting factors, namely the lack of tools to make a driving license due to budget constraints.Keywords: Persoonlijke Vergunning, Driving License, Police